Integration of Modern Medicine and Thibbun Nabawi in Healthcare Services: Opportunities, Challenges, and Implications: English - Zarin Safanah Sihotang (Asian Multidisciplinary Research Journal of Economy and Learning, 2026)
This article critically reviews the possible integration of modern medicine and Thibbun Nabawi in healthcare services by examining conceptual compatibility, clinical evidence, service implementation, and regulatory boundaries. A structured narrative review was conducted using a PRISMA-guided selection process. Literature was searched in Scopus, PubMed, SINTA, and Web of Science for publications from 2015 to 2026, using terms related to prophetic medicine, Islamic health traditions, integrative medicine, and healthcare services. From 142 identified records, 108 remained after duplicate removal, 65 were screened by title and abstract, 42 were assessed in full text, and 28 sources were included for qualitative synthesis. The review shows that integration is most defensible when Thibbun Nabawi is treated as a selective, evidence-sensitive, and ethically bounded complement rather than as a substitute for biomedical care. Cupping, honey, Nigella sativa, and ajwa dates have different levels of clinical plausibility, whereas ruqyah is more appropriately positioned as psychosocial and religious support. Safe implementation requires protocols, practitioner oversight, product standardisation, informed consent, and legal accountability. The article concludes that integration is possible only under clinical, ethical, and regulatory discipline.